Towards a new history for the Egyptian Old Kingdom : perspectives on the pyramid age - Der Manuelian, Peter.; Schneider, Thomas, 1964- (Harvard Egyptological Studies, 2015)
The Pyramid Age represents the first of several highpoints in ancient Egypt's long history. But critical questions remain about the period, its social structure and economic organization, and the long-term implications of its artistic achievements. On the occasion of the fifth anniversary of the Journal of Egyptian History , The University of British Columbia, Harvard University, and Brill Academic Publishers, Boston, held a conference at Harvard University on April 26, 2012. A distinguished group of Egyptological scholars from around the world gathered to consider new perspectives on the Pyramid Age; the results are presented here.